Phosphine/palladium-catalyzed one-pot synthesis of functionalized 6H-benzo[c]chromenes1. Issue 71 (2nd August 2015) - Mo, Hanjie; Pan, Chengmin; Chen, Dingben; Chen, Di; Gao, Jianrong; Yang, Jianguo
<x xml:space="preserve">Abstract</x> Functionalized alkenyl 6H-benzo[c]chromenes are synthesized through a one-pot, phosphine/palladium sequential catalysis reaction with good stereoselectivity.